Managing COPD with expiratory or inspiratory pressure load training based on a prolonged expiration pattern. Issue 3 (31st August 2020) - Miki, Keisuke; Tsujino, Kazuyuki; Miki, Mari; Yoshimura, Kenji; Kagawa, Hiroyuki; Oshitani, Yohei; Fukushima, Kiyoharu; Matsuki, Takanori; Yamamoto, Yuji; Kida, Hiroshi
Background: Exertional prolonged expiration should be identified as a therapeutic target in COPD. The efficacy of expiratory or inspiratory pressure load training (EPT/IPT) based on the degree of prolonged expiration was investigated. Methods: A total of 21 patients with COPD were divided into two groups according to the exertional change in the inspiratory duty cycle ( T I / T tot). For 12 weeks, patients whose exertional T I / T tot decreased received EPT (EPT group, n=11, mean percentage forced expiratory volume in 1 s (%FEV1 ), 32.8%) and those whose exertional T I / T tot increased received IPT (IPT group, n=10, mean %FEV1, 45.1%). Results: The therapeutic responses were as follows. In both groups, endurance time (EPT, +5.7 min, p<0.0001; IPT, +6.1 min, p=0.0004) on the constant work rate exercise test (WRET) and peak oxygen uptake increased (EPT, p=0.0028; IPT, p=0.0072). In the EPT group the following occurred: 1) soon after commencement of exercise with the constant WRET, the expiratory tidal volume ( V T ex) increased, reducing dyspnoea; 2) V T ex and mean expiratory flow increased and then prolonged expiration (p=0.0001) improved at peak exercise with the incremental exercise test (ET); and 3) St. George's Respiratory Questionnaire total, activity and impact scores were improved. In the IPT group, on both the constant WRET and incremental ET, breathing frequency increased, which led to greater exercise performance with effort dyspnoea. Conclusions: This study showed the benefits of EPT/IPT on exercise performance. If the choice of managing COPD with EPT/IPT is appropriate, inexpensive EPT/IPT may become widespread as home-based training. Expiratory or inspiratory pressure load training (EPT/IPT) based on the degree of prolonged expiration improves exercise performance in COPD patients. If managing COPD with EPT/IPT is chosen appropriately, it could become widespread as home-based training. https://bit.ly/2ZWutWq